(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the frequency of common early complications following Omentopexy as primary repair in perforated duodenal ulcer. Materials and Methods: This was a descriptive study of 6 months duration, carried out from Jan 2014 to June 2014 in the department of general surgery, Lady reading hospital peshawar. A total of 144 patients were selected and admitted through emergency. Inclusion and exclusion criteria was set. After detail history and clinical examination ,all patients were investigated and were prepared for emergency laparotomy. A detail proforma has been made which contain all information about the patients. SPSS software (version 17.0) was used for the statistical analysis Results: Our study shows that 9% patients were in age range < 25 years, 28% patients were in age range 26-50 years, 30% patients were in age range 51-75 years while 33% patients were >75 years. Mean age was 48 years with a standard deviation of ±5.71. Seventy three percent patients were male and 27% patients were female. Thirty two percent patients had wound infection and 11% patients had anastomotic leak. Conclusion: Our study concludes that omentopexy with thorough peritoneal lavage is simple and safe procedure with low mortality and post-operative complications